Locule Position and Thawing Duration Affect Postharvest Quality of Freshly Cryo-Frozen Musang King Durian Fruit - Md Nor, Shahidah; Phebe Ding, Phebe Ding; Tan Jit Chun, Tan Jit Chun (Pertanika, 2023)
This study examined the effect of locule position and thawing duration on the physicochemical and nutritional characteristics of intact cryo-frozen Musang King durian fruit. Cryo-frozen durian that had 5 locules was thawed for 2 and 18 hr, and the fruitlets of each locule were analysed for colour (L*, a*, b*, C*, and h°), firmness, soluble solids concentration (SSC), titratable acidity (TA), pH, ascorbic acid (AA), total phenolic content, total flavonoid content, 1,1-diphenyl-2-picrylhydrazyl, 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid and ferric reducing antioxidant power assay (FRAP). Results show that L* and a* of pulp colour, firmness, SSC, pH, TA, AA, and FRAP of cryo-frozen durian fruit were affected by a significant interaction between locule position and thawing duration. It implies the postharvest quality of intact cryo-frozen durian fruitlet distinct from each other due to their locule position and thawing duration.